Intersectionality and Its Relevance in the Context of Aboriginal People with Brain Injury in Australia - Armstrong, Elizabeth; Colegate, Kerri; Papertalk, Lenny; Crowe, Stuart; McAllister, Meaghan; Hersh, Deborah; Ciccone, Natalie; Godecke, Erin; Katzenellenbogen, Judith; Coffin, Juli (Seminars in Speech and Language, 2023)
In this article, we explore the benefits of recognizing the impact of intersectionality on access to, and provision of, brain injury care in a First Nations context. While disadvantage and discrimination are often associated with the intersection of culture, gender, disability, and socioeconomic disadvantage, it is only when these factors are explored together that clinicians can really understand what people need to recover and thrive following acquired brain injury. In this article, we challenge speech-language pathologists to examine their own practices, to look beyond Western models of health and constraints of many current institutional models of care and ways of framing research, to acknowledge historical and ongoing colonizing influences, and to engage with community-led solutions. We provide a model of Aboriginal-led care, where intersection of discrimination and marginalization is minimized and the multiple components of the individual, carers/communication partners, and the environment become empowering factors instead.
Keywords: Aboriginal; First Nations; brain injury; intersectionality; stroke